PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK TAS DAN SEPATU CHARLES & KEITH (Studi Kasus Konsumen Charles & Keith Paragon Semarang) - Asih Fatmawati; Sri Suryoko (Universitas Diponegoro, 2018)
Fashion world is an interesting and important world for most women. Fashion itself is used with various purposes such as, to show identity of the wearer. Charles & Keith is one of the supporting Fashion in the world and it also operates in Semarang. In the last three years Charles and Keith in Semarang has decreased sales in 2014-2016. The Purpose of this research was to know the influence of brand image, product quality, and price on the purchasing decisions of Charles & Keith consumers in Paragon Semarang. The type of this research is Explanatory research. The sampling technique used Accidental Sampling method. The number of samples were taken as many as 100 respondents. The data were analyzed through validity test, reliability test, crosstab, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, t test, and F test with SPSS program. Based on the analysis, shows that the brand image of Charles & Keith is in the